2004
DOI: 10.1289/ehp.7167
|View full text |Cite
|
Sign up to set email alerts
|

Quinones and Aromatic Chemical Compounds in Particulate Matter Induce Mitochondrial Dysfunction: Implications for Ultrafine Particle Toxicity

Abstract: Particulate pollutants cause adverse health effects through the generation of oxidative stress. A key question is whether these effects are mediated by the particles or their chemical compounds. In this article we show that aliphatic, aromatic, and polar organic compounds, fractionated from diesel exhaust particles (DEPs), exert differential toxic effects in RAW 264.7 cells. Cellular analyses showed that the quinone-enriched polar fraction was more potent than the polycyclic aromatic hydrocarbon (PAH)–enriched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
251
4
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 390 publications
(267 citation statements)
references
References 47 publications
7
251
4
5
Order By: Relevance
“…After combustion, this core rapidly cools and organic materials, and transition metals present in the combustion chamber are absorbed onto the particle. Xia et al (31,32) fractionated the organic component of the particles and demonstrated that the fraction enriched in quinones was sufficient to increase oxidant generation in an isolated liver mitochondria preparation. In A549 cells, Li et al (33) showed the accumulation of electron dense granules 1 h after particle administration.…”
Section: Discussionmentioning
confidence: 99%
“…After combustion, this core rapidly cools and organic materials, and transition metals present in the combustion chamber are absorbed onto the particle. Xia et al (31,32) fractionated the organic component of the particles and demonstrated that the fraction enriched in quinones was sufficient to increase oxidant generation in an isolated liver mitochondria preparation. In A549 cells, Li et al (33) showed the accumulation of electron dense granules 1 h after particle administration.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory effects are mediated by the redox-sensitive MAP kinase and NF-κB cascades that are responsible for the expression of cytokines, chemokines, and adhesion molecules, many of which are involved in the inflammatory process of the lung [1,3,14,19]. Tier 3 cytotoxic effects (aka toxic oxidative stress) involve mitochondria, which are capable of releasing pro-apoptotic factors and inducing apoptosis of lung cells [20,21]. Taken together, the hierarchical cellular oxidative stress model provides a mechanistic platform against which to understand how PM generates adverse health effects.…”
Section: The Role Of Oxidative Stress In the Health Effects Of Particmentioning
confidence: 99%
“…For instance, electron microscopy has revealed that UFP are capable of localizing inside damaged mitochondria. Both aromatic organic compounds and quinones contribute to mitochondrial injury and ROS generation [21,22]. Thus, the extent of cellular toxicity is directly related to these organic chemical compounds.…”
Section: Generation Of Oxidative Stress By Ambient Particulate Pollutmentioning
confidence: 99%
See 1 more Smart Citation
“…To this date, however, there appears to be heterogeneity in particulate matter (PM) concentrations and PMassociated health effects between locations within an urban setting, which raises considerable uncertainties as to whether PM mass, number, size, bulk or surface chemistry are the appropriate metrics associated with PM toxicity. For example, recent studies have shown that atmospheric ultrafine particles (with physical diameter o100 nm) have the potential for eliciting adverse health effect (Oberdo¨rster and Utell, 2002;Li et al, 2003Li et al, , 2004Xia et al, 2004). Recent epidemiological studies by Peters et al (1997) have demonstrated a higher association between health effects and exposures to ultrafine particles compared to accumulation mode or coarse particles.…”
Section: Introductionmentioning
confidence: 99%